2018
DOI: 10.1159/000490791
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis of Colorectal Post-Polypectomy Bleeding Due to Antithrombotic Agent

Abstract: Background/Aims: Post-polypectomy bleeding (PPB) is a major complication of colorectal polypectomy, and antithrombotics is one of the major risk factors of PPB. The purpose of this study was to investigate PPB risks with regard to the combinations of antithrombotic agents used. Methods: We retrospectively reviewed cases involving colonoscopic polyp resection between September 2002 and December 2014. The risk of PPB was assessed according to patient and lesion factors, including antithrombotic use. Antithrombot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
(37 reference statements)
3
15
1
Order By: Relevance
“…There were some limitations to the study, one of which is the retrospective single‐center study design; eg, the distribution of patients was unequal among the groups, and the sample size of the DAPT and anticoagulant users was relatively small, which might have affected the liability in the statistical analyses (see the wide 95% CI in the logistic model) and undermined the value of extrapolating these results to clinical practice. However, similar results have also been noticed in studies 11,29 with sample sizes of HB therapy ranging from 20 to 45. Although these patients are relatively uncommon in clinical setting, our findings, along with those of other studies, imply that use of HB therapy warrants more caution than it has hitherto received.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There were some limitations to the study, one of which is the retrospective single‐center study design; eg, the distribution of patients was unequal among the groups, and the sample size of the DAPT and anticoagulant users was relatively small, which might have affected the liability in the statistical analyses (see the wide 95% CI in the logistic model) and undermined the value of extrapolating these results to clinical practice. However, similar results have also been noticed in studies 11,29 with sample sizes of HB therapy ranging from 20 to 45. Although these patients are relatively uncommon in clinical setting, our findings, along with those of other studies, imply that use of HB therapy warrants more caution than it has hitherto received.…”
Section: Discussionsupporting
confidence: 85%
“…In Chinese patients, left colon and rectal neoplasms are more common 28 than they are in Western populations. The incidence of DPPB was higher for rectal polyps, possibly because of the abundant blood vessels in the rectal mucosa, and similar results have been reported in a Japanese study 29 . Almost half of DPPB cases do not require therapeutic intervention 30 .…”
Section: Discussionsupporting
confidence: 78%
“…We found 2417 articles, removing 186 duplicated records, excluding 2195 records based on their titles and abstracts. Among the 37 full texts assessed for eligibility, we included 8 articles (7 full-text and 1 abstract) for the quantitative synthesis, including 1,620 patients on antiplatelet therapy (P2Y12i or Aspirin) and 13,321 controls [20][21][22][23][24][25][26][27]. The characteristics of the eight selected studies are reported in Table 1 and in Supplementary Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies used a retrospective design [20][21][22][25][26][27], while two used a prospective design [23,24]. Six studies included both aspirin and P2Y12i users.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent report, the risk of DPPB requiring endoscopic hemostasis is low after HSP removal of 4-9-mm adenomatous polyps (0.5%, 2 of 402 polyps) in patients not using antithrombotic therapy [3]. Yet, the risk was markedly increased in patients taking antithrombotic drugs [4], and the combined use of multiple antithrombotic agents puts patients at an even higher risk [5]. Current practice guidelines consider polypectomy a high-risk procedure in patients requiring long-term antithrombotic agents, recommending temporary withdrawal of these agents prior to polypectomy, increasing the risk of thrombotic complications [6].…”
mentioning
confidence: 99%